Suspension of payments, bank failures, and the nonbank public's losses - Jr. Gerald P. Dwyer; Iftekhar Hasan (Federal Reserve Bank of Atlanta, 1996)
Arguably, eliminating suspensions of payments–periods when banks jointly refuse to convert their liabilities into outside money or other assets–was an important impetus for creating the Federal Reserve. Friedman and Schwartz suggest that a suspension in 1930 would have decreased the severity of the Great Depression. More recently, an emerging literature suggests that suspensions of payments may well be optimal in some states of the world. We present evidence about suspensions of payments from an episode that is close to a controlled experiment for examining their effects. In 1861, about 44 percent of the banks in Wisconsin closed, 81 percent of the banks in Illinois closed, and noteholders suffered substantial losses. The historical record suggests a possible explanation: an effective suspension of payments in Wisconsin but not Illinois. Historical and statistical evidence indicate that the suspension of payments decreased the number of banks that closed as well as noteholders' losses. Our statistical evidence indicates a 25 percent increase in the probability that an average bank in the two states remains open with the suspension of payments. The suspension of payments decreases noteholders' losses by about 20 cents per dollar of notes.
Keywords: 330; Bank failures; Banks and banking - History; Banks and banking; Central